Sistem Kontrol dan Monitoring Ph Air serta Kepekatan Nutrisi pada Budidaya Hidroponik Jenis Sayur dengan Teknik Deep Flow Techcnique - Moses Gregoryan Ndolu Eoh; Justinus Andjarwirawan; Resmana Lim (Jurnal Infra, 2019)
The development of information technology is increasingly advanced and fast. Many technologies go into other fields such as agriculture. The most frequently used technology is IoT. All forms of IoT Technology will relate to the internet. This technology can facilitate people in the field of agriculture such as making hydroponic nutrients automatically with the website application. Obviously this technology requires microcontroller tools, sensors and other robotic tools.To connect with censorship tools and website applications, microcontrollers are required as a control center. Creating a website application using the PHP programming language. As for microcontrollers use the C++ programming language. On the website will be displayed data in graphic form. The process of sending sensor data to a website via a local server. The microcontroller used is Wemos D1R1 which has a wifi module.The result of this research is the microcontroller managed to run well with the website application. PH control and monitoring system, the concentration and volume of water running according to the setpoint specified by user. User Interface which is simple and easy to understand.